A Case of Palmoplantar Keratodermas Complicated by Pseudoainhum and Literature Review - Ye J; Li W; Yang X; Shi Y; Lv W (Clinical, Cosmetic and Investigational Dermatology)
Junhong Ye,1 Wen Li,1 Xianxu Yang,1 Yanhai Shi,2 Wen Lv3 1Department of Plastic Surgery and Skin Disease, Hainan Fifth People’s Hospital, Haikou City, Hainan Province, People’s Republic of China; 2Department of Skin Disease, Qionghai People’s Hospital, Qionghai City, Hainan Province, People’s Republic of China; 3Department of Allergy, Hainan Fifth People’s Hospital, Haikou City, Hainan Province, People’s Republic of ChinaCorrespondence: Wen Lv, Email 18876177295@163.comAbstract: A 43-year-old man who had presented diffuse plaques on both hands and feet for 10 years and constriction of the fifth digit of the right foot for 1 year was included in this case report. Diffuse hyperplastic yellow-brown plaques were observed in the palms of both hands and soles of both feet in this man. Yellowish crusting formed on the plaques. There was much white debris on the surface lesions. The fifth phalanx of the right foot was ring-shaped and narrowed, and the toe was globular. Color Doppler ultrasound examination revealed arteriosclerosis and multiple small plaques in the right lower limb vessel. An antero-posterior radiograph of the right foot showed constriction of the fifth phalanx. The man was diagnosed with palmoplantar keratodermas complicated by pseudoainhum.Keywords: pseudoainhum, palmoplantar keratosis, dermatosis